Pengaruh Kepala Sekolah dalam Pengelolaan Pendidikan di Sekolah Dasar - Mevi Tasya Mevlevi; Prihartini Prihartini; Kuswanto Kuswanto (Universitas Indraprasta PGRI Jakarta, 2021)
Within the scope of the educational unit organization in elementary schools, the role of principal is needed. However, the fact is that the school principal only hunts for positions and is less proficient in management. Even though as a leader has a role that affects teacher performance and school quality. The authors aims to describe the role of the principal and the need for education management by using descriptive method through reading books and journals, it was found that the principal had an influence in the management of education in primary schools for teacher performance and learning outcomes.